Comparing clinicians' use of an anticoagulation management service and usual care in ambulatory oncology. (September 2013) - Weingart, Saul N; Cleary, Angela; Scullion, Bridget; Morway, Laurinda; Phantumvanit, Victor; Stuver, Sherri O; Shulman, Lawrence N; Connors, Jean M
Purpose: There is no consensus in the oncology community about the optimal model for anticoagulation management of ambulatory cancer patients. To understand oncologists' preferences regarding anticoagulation management, we compared the characteristics of patients referred to an oncology-oriented anticoagulation management service with "usual care" patients managed by the patient's primary oncologist. Methods: We performed a retrospective medical record review of ambulatory oncology patients' anticoagulation care at a comprehensive cancer center. We examined the characteristics of 33 patients anticoagulated before implementation of a dedicated oncology anticoagulation management service. We compared this group with 33 patients managed by the anticoagulation management service and with 39 usual care patients managed by the primary oncologist after the anticoagulation management service was created. We also examined differences in laboratory test utilization, time in the therapeutic range (for patients anticoagulated with warfarin), and anticoagulation-related adverse events during a 3-month assessment period. Results: Anticoagulation management service patients were more likely to be treated for hematologic malignancies, use erythropoietin stimulating agents, and require warfarin management for previous venous thromboembolic disease compared to usual care patients. In contrast, oncologists were more likely to manage anticoagulation care of patients with advanced solid tumors undergoing active chemotherapy. Anticoagulation management service and usual care patients on warfarin therapy had comparable time in the therapeutic range and complication rates. Conclusion: Oncologists selectively referred patients to the anticoagulation management service. Anticoagulation management service patients' warfarin control and complication rates were comparable to care provided by the primary oncologist, suggesting that an oncology-specific anticoagulation management service may be a feasible and effective option for anticoagulation management of ambulatory oncology patients.